Aplikasi Visualisasi Data Berbasis Web dengan Deteksi Otomatis Tipe Data untuk Mendukung Analisis Informasi - Priyangan, Donny Muda (Jurnal Instrumentasi dan Teknologi Informasi (JITI), 2025)
The rapid growth of data-driven decision making requires systems capable of managing and presenting data in an effective, flexible, and user-friendly manner. However, variations in dataset characteristics, such as numerical and categorical data, often pose challenges in selecting appropriate visualization techniques. Therefore, this study designs and develops a web-based data visualization application equipped with an automatic data type detection mechanism. The system is able to identify data types automatically and determine suitable visualization forms, including bar charts, line charts, pie charts, histograms, radar charts, and polar area charts. The developed application allows users to import datasets, monitor data quality, and perform interactive visual analysis. The implementation results indicate that the system can present various types of datasets in a structured manner and assist users in understanding data patterns, trends, and characteristics more quickly and intuitively. Thus, this application supports visual analytics processes and enhances the effectiveness of information analysis.